A CRITICAL EXAMINATION OF AMITAV GHOSH’S WORKS: LITERARY THEMES, NARRATIVE METHODS AND HISTORICAL CONSCIOUSNESS - Choudhary, Garima; Kumar, Ravinder (ShodhKosh: Journal of Visual and Performing Arts, 2023)
With an emphasis on Amitav Ghosh’s narrative techniques, thematic concerns, and engagement with history, climate change, and postcolonial identities, this paper critically analyzes his literary works. A distinct place in modern literature is created by Ghosh’s works, which combine historical realism and fiction in The Ibis Trilogy, The Shadow Lines, and The Great Derangement. The essay looks at how his writing questions traditional historiography, investigates intercultural interactions and tackles urgent global concerns like environmental crises. This paper is an honest attempt to draw reader’s attention to the role of Amitav Ghosh in the literary world. This paper examines his thematic concerns, narrative strategies and sociopolitical engagements, emphasizing his role in reshaping modern literary discourse. This study takes an interdisciplinary approach to highlight Ghosh’s contributions to contemporary world literature, as well as his influence on discussions about historical memory, identity and ecological consciousness.